Mild Traumatic Brain Injury: Longitudinal Study of Cognition, Functional Status, and Post-Traumatic Symptoms - Dikmen, Sureyya (J Neurotrauma, 2017)
More than 75% of traumatic brain injuries (TBIs) seeking medical attention are mild, and outcome in that group is heterogeneous. Until sensitive and valid biomarkers are identified, methods are needed to classify mild TBI into more homogeneous subgroups. Four hundred twenty-one adults with mild TBI were divided into groups based on Glasgow Coma Scale (GCS) 13–15 without computed tomography (CT) abnormalities, GCS 15 with CT abnormalities, and GCS 13–14 with CT abnormalities, and were compared with 120 trauma controls on 1-month and 1-year outcomes. At 1 month post-injury, almost all neuropsychological variables differed significantly among the groups. Compared with trauma controls, the GCS 13–15 CT normal group showed no significant differences on any neuropsychological measure or Glasgow Outcome Scale (GOS). The GCS 15 CT abnormal group performed significantly worse on only a measure of episodic memory and learning (Selective Reminding Recall [SRCL]) and GOS, and the GCS 13–14 CT abnormal group performed significantly worse on most neuropsychological measures and GOS. At 1 year post-injury, except for an isolated difficulty on SRCL in the GCS 13–14 CT abnormal group, no differences were observed on any neuropsychological measures nor on GOS. Mean percent of total post-traumatic symptoms endorsed as new or worse and percent endorsing three or more symptoms differed significantly (p < 0.001), with each TBI subgroup reporting significantly more symptoms than the trauma controls at both 1 month and 1 year. In conclusion, this subgrouping improves granularity within mild TBI. While most neuropsychological and functional differences abate by 1 year, reporting three or more post-traumatic symptoms remain for about half of individuals.